2020
DOI: 10.3390/antiox9020121
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Protects Human Trophoblast HTR8/SVneo Cells from H2O2-Induced Oxidative Stress by Activating Nrf2 Signaling Pathway

Abstract: Pregnancy complications are associated with oxidative stress induced by accumulation of trophoblastic ROS in the placenta. We employed the human trophoblast HTR8/SVneo cell line to determine the effect of curcumin pre-treatment on H2O2-induced oxidative damage in HTR8/Sveo cells. Cells were pretreated with 2.5 or 5 μM curcumin for 24 h, and then incubated with 400 μM H2O2 for another 24 h. The results showed that H2O2 decreased the cell viability and induced excessive accumulation of reactive oxygen species (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 57 publications
1
29
0
Order By: Relevance
“…Through literature study on the antioxidant activity of Hippophae, it was found that the DPPH assay is used in a large proportion of experiments verifying the antioxidant activities of Hippophae. However, some studies have shown that the kinetic analysis of DPPH as an antioxidant activity test has been questioned; especially, the significance of antioxidants detected by DPPH in the human body needs to be further confirmed [63]. In addition, the establishment of animal models has greatly contributed to the development of medicines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Through literature study on the antioxidant activity of Hippophae, it was found that the DPPH assay is used in a large proportion of experiments verifying the antioxidant activities of Hippophae. However, some studies have shown that the kinetic analysis of DPPH as an antioxidant activity test has been questioned; especially, the significance of antioxidants detected by DPPH in the human body needs to be further confirmed [63]. In addition, the establishment of animal models has greatly contributed to the development of medicines.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear factor erythroid 2-related factor 2 (Nrf2) is a key transcription factor of the cellular antioxidative stress system [63]. Moreover, Nrf2 nuclear translocation combined with antioxidative response element antioxidant responsive element (ARE) on the nucleic acid sequence is a key link in the activation of Nrf2-ARE signaling pathways [64].…”
Section: Effects On Cell Antioxidant Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that pretreatment with curcumin (5 µM for 24 h) increased cell viability, upregulated the activities of the antioxidant enzymes CAT and glutathione peroxidase (GSH-Px), reduced the H 2 O 2 -induced ROS accumulation and the apoptotic rate. At molecular levels, these data were associated with an increased nuclear translocation of the antioxidant transcription factor Nrf2, and reduced expression of cleaved-caspase 3 [ 52 ].…”
Section: Role Of Curcumin In Pregnancymentioning
confidence: 99%
“…The upsurge in ROS induced by drugs is lined to activation of several pathological cell processes such as unprogramed cell death, inflammation, and chain reactions (Qi, Jiang, Zhang, Zhang, & Wang, 2020). The brain chiefly composed of fats, having high energy demand, and weak antioxidant capacity is easily prone to oxidative damage (Lakroun et al, 2015).…”
mentioning
confidence: 99%